Organocatalytic synthesis of enantioenriched 1, 2, 4-triazolines containing a chiral quaternary carbon center. Issue 30 (28th March 2017) - Zhang, Li-Jun; Zhang, Si-Xiang; Fu, Li-Na; Li, Xiao-Yun; Guo, Qi-Xiang
Abstract : A tertiary amine catalyzed asymmetric cyclization of isothiocyanates and azodicarboxylates towards the synthesis of chiral 1, 2, 4-triazolines has been described. Abstract : An efficient asymmetric cyclization reaction of amino-acid-derived isothiocyanates with azodicarboxylates is described. The chiral 1, 2, 4-triazolines are prepared in good yield (up to 87%) and enantioselectivities (up to 95% ee).